2009
DOI: 10.1302/0301-620x.91b12.22418
|View full text |Cite
|
Sign up to set email alerts
|

Femoral lengthening in achondroplasia

Abstract: Extensive limb lengthening may be indicated in achondroplastic patients who wish to achieve a height within the normal range for their population. However, increasing the magnitude of lengthening is associated with further complications particularly adjacent joint stiffness and fractures. We studied the relationship between the magnitude of femoral lengthening and callus pattern, adjacent joint stiffness and fracture of the regenerate bone in 40 femoral lengthenings in 20 achondroplastic patients. They were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 16 publications
3
34
0
4
Order By: Relevance
“…While the underlying diagnoses, limb segments lengthened, and devices used for lengthening were available for all subjects, other variables such as patient age, sex, preoperative height, and length gained were not found on a consistent basis for all studies. 7 of the 18 studies dealt with tibial lengthening only (Cattaneo et al 1988, Noonan et al 1997, McAllister et al 1999, Hahn et al 2003, Catagni et al 2005, Vaidya et al 2006, Park et al 2008), 2 studies (Venkatesh et al 2009, Kim et al 2012a) dealt with femoral lengthening alone, and the remaining 9 studies included patients undergoing combined tibial and femoral lengthening procedures. The average age of the patients at surgery was 16.3 (4–47) years and the mean follow-up time was 4.3 (0.8–16) years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the underlying diagnoses, limb segments lengthened, and devices used for lengthening were available for all subjects, other variables such as patient age, sex, preoperative height, and length gained were not found on a consistent basis for all studies. 7 of the 18 studies dealt with tibial lengthening only (Cattaneo et al 1988, Noonan et al 1997, McAllister et al 1999, Hahn et al 2003, Catagni et al 2005, Vaidya et al 2006, Park et al 2008), 2 studies (Venkatesh et al 2009, Kim et al 2012a) dealt with femoral lengthening alone, and the remaining 9 studies included patients undergoing combined tibial and femoral lengthening procedures. The average age of the patients at surgery was 16.3 (4–47) years and the mean follow-up time was 4.3 (0.8–16) years.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that patients with achondroplasia tolerate lengthening very well because of their ligament and soft tissue laxity, and their muscle length exceeds bone length before lengthening (Paley 1988). Lengthening of more than 30% was often reported in A/H patients (Aldegheri et al 1988, McAllister et al 1999, Venkatesh et al 2009, Devmurari et al 2010). In the pooled analysis, the mean gain in height (10cm) and LP (36%) was greater in patients with A/H than in patients with other diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously recommended temporary cessation of distraction and the application of gradual compression when concave, lateral or central callus shapes appear in the regenerate bone, until satisfactory regenerate with fusiform callus develops. 12 Some of the dissatisfaction expressed by patients with a lengthened lower limb may be attributed to the effects of upper-and lower-limb mismatch. 25,26 Someone with short arms and lengthened lower limbs will have difficulty in donning and removing socks, shoes or underwear.…”
Section: Discussionmentioning
confidence: 99%
“…11 We have also suggested that careful radiological assessment of the patterns of callus formation is a useful method for the evaluation and monitoring of regenerate bone. 12 Using these methods, we wished to investigate the difference in callus maturation between humeral lengthening and femoral lengthening.…”
mentioning
confidence: 99%